Infrastructure alone cannot ensure resilience to weather events in drinking water supplies - Charles, K; Howard, G; Villalobos Prats, E; Et al. (Elsevier, 2021)
Climate resilient water supplies are those that provide access to drinking water that is sustained through seasons and through extreme events, and where good water quality is also sustained. While surface and groundwater quality are widely understood to vary with rainfall, there is a gap in the evidence on the impact of weather and extremes in rainfall and temperature on drinking water quality, and the role of changes in water system management. A three-country (Bangladesh, Nepal and Tanzania) observational field study tracked 2353 households clustered around 685 water sources across seven different geographies over 14 months. Water quality (E. coli) data was modelled using GEE to account for clustering effects and repeated measures at households. All types of infrastructure were vulnerable to changes in weather, with differences varying between geographies; protected boreholes provided the greatest protection at the point of collection (PoC). Water quality at the point of use (PoU) was vulnerable to changes in weather, through changes in PoC water quality as well as changes in management behaviours, such as safe storage, treatment and cleaning. This is the first study to demonstrate the impact of rainfall and temperature extremes on water quality at the PoC, and the role that weather has on PoU water quality via management behaviours. Climate resilience for water supplies needs to consider the infrastructure as well as the management decisions that are taking place at a community and household level.